The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

La fabrique du sexe : essai sur le corps et le genre en Occident - Laqueur, Thomas Walter (NRF essais, 1992)
L'Occident n'a cessé depuis les origines de s'interroger sur la différence des sexes. Mais parle-t-on de l'homme et de la femme que l'on n'a encore rien dit : se réfère-t-on au genre - définition culturelle par des qualités morales, affectives, sociales... - ou au sexe - définition par des spécificités anatomiques ? Jamais, en effet, les deux notions ne se recouvrirent, rappelle Thomas Laqueur dans cet ouvrage qui demeure une référence majeure. Dès l'Antiquité, Aristote, par la définition de l'ordre des êtres, et Galien, par la définition du corpus anatomique, fondent le modèle du sexe unique, qui sera dominant jusqu'au XVIIIe siècle, et dans lequel le genre définit le sexe. Au XVIIIe siècle émerge l'autre modèle de la différence sexuelle, le modèle des deux sexes, dans lequel, au contraire du premier, le sexe définit le genre : parce que, au niveau de l'anatomie comme de la physiologie, femmes et hommes sont incommensurablement différents, les genres définissent dès lors qualités, vertus et rôles selon des racines biologiques. Ces deux modèles coexistent dans le temps - dès le XVIe siècle des auteurs posent l'irréductible différence anatomique, alors qu'au XXe siècle encore Freud pense la sexualité selon le modèle du sexe unique - car leur prégnance sur les esprits, si elle est liée à des évolutions générales - économiques, culturelles, sociales -, ne peut en aucun cas être strictement expliquée par celles-ci; et moins encore par les progrès de la connaissance anatomique, qui se moulent le plus souvent dans les représentations dictées par chacun de ces modèles...
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; corps; cours; discipline; discours dominant; essentialisme; féminisme matérialiste; genre; histoire; histoire et politique; hétérosexisme; occident; philosophie politique; premier cycle; production des savoirs; périodes historiques; sciences humaines; sciences sociales; sex1183; sex3383; sexe/genre; sexualité; systèmes d'oppressions; thématiques; épistémologie